The Processes of Ethnic Identity Reconstruction among the Karen Ethnic Group in Galyani Vadhana District, Chiang Mai Province - Rojkanarach, Phisit; Nawarat, Nongyao; Nasee, Pisith; Buadaeng, Kwanchewan; Warder, Thien (Community and Social Development Journal, 2025)
This study endeavors to explore the ethnic identity reconstruction through practices implemented in Galyani Vadhana’s schools. It aims to explore how cultural knowledge is developed in educational environments using the framework of Culturally Responsive Pedagogy (CRP). It seeks to examine the methods used and offer insights into the knowledge and changes occurring within these communities. Employing qualitative methods, the research centers on two primary objectives: first, to examine the impact of CRP on promoting ethnicity identity reconstruction among Karen people including students, teachers and communities in the schools setting in Galyani Vadhana disrruct, Chiang Mai province; and second, to study the participation of Karen ethnic groups in educational institutions in fostering the reconstruction of Karen ethnic identities within schools. The key informants included teachers, students, and community members from a school at the study site. Data were collected through interviews and observations, then analyzed using a phenomenological approach. The research underscores the importance of reconstructing ethnic identity among the Karen people, particularly within the educational context of Galyani Vadhana district. Collaboration between schools and the Karen communities is essential for fostering ethnic identity through a CRP. This approach involves developing a curriculum that aligns with community needs, embeds cultural values, and enhances the self-esteem of Karen students, teachers, and community members. By doing so, it reduces marginalization and preserve local heritage within the Thai education system. Second, active participation of the Karen ethnic group in educational institutions plays a significant role in promoting ethnic pride and identity reconstruction. The research suggests that increasing the representation of local Karen teachers, as opposed to Thai lowlander teachers who frequently relocate, could provide more continuity and cultural relevance in education. However, it is noted that ethnic minority teachers are underrepresented in the schools, partly due to the lack of emphasis on ethnic identity concepts in their teacher training programs. To address this gap, integrating multicultural education into university curricula for student teachers is essential for fostering a deeper understanding and appreciation of ethnic identity within educational institutions.